HELLP Syndrome Complicated with Postpartum Subcapsular Ruptured Liver Hematoma and Purtscher-Like Retinopathy - Daniela Cernea; Alice Dragoescu; Marius Novac (Case Reports in Obstetrics and Gynecology)
Purtscher's retinopathy is usually associated with trauma, acute pancreatitis, vasculitis, lupus, and bone fractures. It was rarely described postpartum in patients with preeclampsia as well as associated with HELLP syndrome. We present a case of a multiparous patient aged 44 with severe preeclampsia and postpartum HELLP syndrome complicated with Purtscher-like retinopathy and large ruptured subcapsular liver hematoma that required emergency abdominal surgery after premature delivery of a dead fetus. Postsurgical outcome was favorable regarding both liver function and visual acuity.